Эффективность методов синтеза последовательностей со свойством «не более одного совпадения» - Nevrev, A. I.; Galchenkov, O. N. (PE "Politekhperiodika", Book and Journal Publishers, 2016)
The author presents an expression for determining the minimum possible length of binary sequences with "not more than one coincidence" property. Obtained low bound length value allows quantitatively estimating efficiency of any known synthesis methods for creation of binary sequences with "not more than one coincidence" property. The efficiency of known methods of creating binary sequences based on extended Galois fields theory is analysed by comparing the obtained sequences length with a theoretical low bound estimation. The paper shows high performance of the known methods of creation of sequences with "not more than one coincidence" property based on extended Galois fields.